Mosque visit shows willingness to forge ties - News Straits, Times (New Straits Times, 2014)
KUALA LUMPUR: United States President Barack Obama's visit to Masjid Negara is a reflection of Washington's acceptance of Islamic nations aswell as its willingness to forge ties with moderate Muslim countries.Analysts believe that the US president's visit could also lead to greater development for Muslim countries in the future.